SOME BIOLOGICAL OBSERVATIONS ON A HORNET Vespa tropica var. pulchra (Du Buysson), with special reference to its dependence on Polistes wasps - SHOICHI F SAKAGAMI (Research Center for Biology, 1957)
abstract not available